Fuel Cell systems in hybrid-electric aircraft - Meindl, Markus; Forster, Fabian; Eckardt, Bernd; März, Martin (European Electrolyser & Fuel Cell Forum (EFCF), 2025)
With their actual power densities, fuel cell systems are too heavy for aviation. The power density of a fuel cell system can be increased by further developing the subcomponents. Intelligent integration of individual components in the aircraft could be a solution. For this purpose, the aircraft dimensions and simulations of 200 nmi and 600 nmi range from an EU project are used. A more granularly divided series connection of fuel cell systems is considered to integrate these systems in the aircraft more intelligently. A smart way is to equip each fuel cell system with a 640 V (323 kW) system voltage and specially integrated DC-DC boost converters. This choice of system voltage and the use of DC-DC boost converters allow for thinner cross-section cables, easier integration of DC-DC converters into the FC systems housing, and increased system redundancy. The overall control of the fuel cell systems can be carried out via low-weight CAN bus low-voltage signal cables, which hardly contribute to the aircraft's weigh
Keywords: EFCF2025; H2; LowTemp. Fuel Cells & Electrolysers; hybrid-electric aircraft; fuel cells; fuel systems; system integration